1966
DOI: 10.1017/s0034412500002419
|View full text |Cite
|
Sign up to set email alerts
|

Questions about the Meaning of Life

Abstract: Claims about ‘the meaning of life’ have tended to be made and discussed in conjunction with bold metaphysical and theological affirmations. For life to have meaning, there must (it is assumed) be a comprehensive divine plan to give it meaning, or there must be an intelligible cosmic process with a ‘telos’ that a man needs to know if his life is to be meaningfully orientated. Or, it is thought to be a condition of the meaningfulness of life, that values should be ultimately ‘conserved’ in some way, that no evil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 1 publication
0
10
0
2
Order By: Relevance
“…Как показывают некоторые авторы, поиск смысла редко подчиняется логическим правилам, а потому попытки создать точную дефиницию смысла могут завести в тупик. По выражению Р. Хэпбарна, «жизнь -это не высказывание», и ее нельзя объяснить, исходя из лингвистического контекста [6,262]. В частности, как бы вопреки упомянутым выше «психологической» и «социологической» парадигмам, философский анализ обнаруживает, что смысл жизни не сводится к ее этической ценности или даже к счастью [16].…”
Section: амальгамная концепция смыслаunclassified
See 1 more Smart Citation
“…Как показывают некоторые авторы, поиск смысла редко подчиняется логическим правилам, а потому попытки создать точную дефиницию смысла могут завести в тупик. По выражению Р. Хэпбарна, «жизнь -это не высказывание», и ее нельзя объяснить, исходя из лингвистического контекста [6,262]. В частности, как бы вопреки упомянутым выше «психологической» и «социологической» парадигмам, философский анализ обнаруживает, что смысл жизни не сводится к ее этической ценности или даже к счастью [16].…”
Section: амальгамная концепция смыслаunclassified
“…Каким именно образом человек наделяет значением действительность, на чем строит понимание собственной жизни и мироздания в целом? Хотя, по мнению некоторых авторов, распад становится началом рекомпозиции в культуре ее ключевых смысловых систем [6], мы все еще не вполне изучили отвечающие за это механизмы.…”
unclassified
“…Yalom described meaning as a way to relieve personal anxiety, to provide structure in people's lives, and to assist an individual in describing what he or she values in life (Yalom, 1980). According to Hepburn (1965), one way individuals find meaning in life is through cosmic meaning, or the belief that a higher power has laid out a plan for each individual that involves a specified role in the grand design (Hepburn, 1965). Hepburn also stated that personal meaning, in contrast, can be obtained through finding a home, companionship, freedom, service to others, self-realization, and enlightenment.…”
Section: Existentialismmentioning
confidence: 99%
“…Therefore, only a few notable philosophers will be discussed. One quintessential example is the philosopher Jean-Paul Sartre who said, "All existing things are born for no reason, continue through weakness and die by accident…It is meaningless that we are born; it is meaningless that we die" (as cited in Hepburn, 1981 Meaning (1984), recounted his experiences as a Jew in Nazi concentration camps. Although he had been studying the concept of meaning before living through the terrors of the Holocaust, the experience provided new insights on the subject.…”
Section: Development Of the Concept Of Meaning In Lifementioning
confidence: 99%
“…In concurrence with this finding, previous research has identified relationships with others as one of the most important sources of meaning. In studies on the aspects of life that people spontaneously report as meaningful, relationships were consistently the single most frequently rated source of meaning, ranging from 36% to 70% of the responses (DePaola & Ebersole, 1995;DeVogler & Ebersole, 1980, 1981Jenerson-Madden, Ebersole, & Romero, 1992;Taylor & Ebersole, 1993) In addition, Debats, Drost, and Hansen (1995) found that meaningful situations often involved positive contact with others, whereas meaningless situations often involved alienation from others. Krause (2007) found that among older adults, greater anticipated support from others and greater emotional support were associated with a deeper sense of meaning, whereas negative interactions with others were found to lower the sense of life meaning.…”
Section: Main Analysesmentioning
confidence: 99%